Perlindungan Privasi Digital dalam Era Digital : Analisis UU No. 19 Tentang Perubahan UU No. 11 Tahun 2008 pada Pemerintahan Joko Widodo - Prioni Rahmanda Saputri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid development of digital technology in the era of the Fourth Industrial Revolution has significantly impacted Indonesia’s legal framework, particularly concerning digital privacy protection. This study aims to analyze the effectiveness of Undang-Undang Nomor 19 Tahun 2016 as an amendment to Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (UU ITE) in protecting digital privacy during the administration of President Joko Widodo. This research uses a normative legal method with a statutory and content analysis approach to examine digital legal policy. The findings show that, although there have been advances in regulation and law enforcement, digital privacy protection in Indonesia remains fragmented and has not fully adapted to the dynamic development of technology. The absence of a comprehensive legal framework and delays in the enactment of a dedicated data protection law are major challenges. The implications of this study highlight the urgency of formulating more progressive and holistic legal policies, along with adaptive regulations to ensure the protection of individual rights in the digital sphere.